Lack of interleukin-13 receptor α1 delays the loss of dopaminergic neurons during chronic stress - Simone Mori; Shuei Sugama; William Nguyen; Tatiana Michel; M. Germana Sanna; Manuel Sanchez-Alavez; Rigo Cintron-Colon; Gianluca Moroncini; Yoshihiko Kakinuma; Pamela Maher; Bruno Conti (Journal of Neuroinflammation, 2017)
Abstract Background The majority of Parkinson’s disease (PD) cases are sporadic and idiopathic suggesting that this neurodegenerative disorder is the result of both environmental and genetic factors. Stress and neuroinflammation are among the factors being investigated for their possible contributions to PD. Experiments in rodents showed that severe chronic stress can reduce the number of dopaminergic neurons in the substantia nigra pars compacta (SNc); the same cells that are lost in PD. These actions are at least in part mediated by increased oxidative stress. Here, we tested the hypothesis that the interleukin-13 receptor alpha 1 (IL-13Rα1), a cytokine receptor whose activation increases the vulnerability of dopaminergic neurons to oxidative damage, participates in the stress-dependent damage of these neurons. Methods Mice were subject to daily sessions of 8 h (acute) stress for 16 weeks (5 days a week), a procedure previously showed to induce loss of dopaminergic neurons in the SNc. The source and the kinetics of interleukin-13 (IL-13), the endogenous ligand of IL-13Rα1, were evaluated 0, 1, 3, 6, and 8 h and at 16 weeks of stress. Identification of IL-13 producing cell-type was performed by immunofluorescent and by in situ hybridization experiments. Markers of oxidative stress, microglia activation, and the number of dopaminergic neurons in IL-13Rα1 knock-out animals (Il13ra1 Y/ − ) and their wild-type littermates (Il13ra1 Y/+ ) were evaluated at 16 weeks of stress and at 20 weeks, following a 4 week non-stressed period and compared to non-stressed mice. Results IL-13 was expressed in microglial cells within the SN and in a fraction of the tyrosine hydroxylase-positive neurons in the SNc. IL-13 levels were elevated during daily stress and peaked at 6 h. 16 weeks of chronic restraint stress significantly reduced the number of SNc dopaminergic neurons in Il13ra1 Y/+ mice. Neuronal loss at 16 weeks was significantly lower in Il13ra1 Y/− mice. However, the loss of dopaminergic neurons measured at 20 weeks, after 4 weeks of non-stress following the 16 weeks of stress, was similar in Il13ra1 Y/+ and Il13ra1 Y/− mice. Conclusions IL-13, a cytokine previously demonstrated to increase the susceptibility of SNc dopaminergic neurons to oxidative stress, is elevated in the SN by restraint stress. Lack of IL-13Rα1 did not prevent nor halted but delayed neuronal loss in the mouse model of chronic restraint stress. IL-13/IL-13Rα1 may represent a target to reduce the rate of DA neuronal loss that can occur during severe chronic restraint stress.